Prevalence Of Patellofemoral Pain Syndrome In Asha Workers - Misal, Kareena; Patil, Maithili; More, Kinjal (Journal of Neonatal Surgery, 2025)
Background Asha workers are frontline community health worker who has to be the inhabitants of the village, ideally between the ages of 25 to 45. Syndrome of Patellofemoral Pain is described as aching behind or around the patella that escalates after at least a single activity that strains the patella after bearing weight with the knee bent. It aims to investigate the prevalence of PFPS in ASHA employees. Method ASHA workers having anterior knee pain underwent evaluation by using NPRS, Clarke’s sign and Kujala knee pain Score. Data on age, years of experience and duration of work was taking in consideration. participants with patellar instability, lower limb fracture and previous knee surgery were excluded. Result in this study 73 participants were included out of which 52 participants had positive Clarke’s sign and 22 had negative clarke’s sign. Most of the participants They ranged among the ages of 25 and 40, having a mean age around 33.85(±4.74) years with experience of 5 or more years. there was significant correlation between kujala akps and clarke’s sign. Conclusion this study predicts the susceptibility of pfps in asha workers. asha worker are more prone for pfps which suggests high risk of injury. asha worker’s severe workload has a substantial influence on their ability to provide quality healthcare services to the community as well as their own health. knee joint is weight bearing joint and so it is more prone injuries.